2018
DOI: 10.1111/tmi.13023
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the delay of diagnosis of leprosy in north‐eastern Colombia: a quantitative analysis

Abstract: Our study found a significant delay in diagnosis of leprosy in north-eastern Colombia, which might explain the continuously high rate of DG2 among new cases being notified in the country. Both patient- and health system-related factors were associated with longer diagnostic delay. Interventions to increase awareness of disease among the general population and timely referral to a specialised health professional are urgently needed in our study setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 10 publications
1
43
0
9
Order By: Relevance
“…Ignorance of illness or waiting for the disappearance of the symptom by itself was the major reason for not seeking help in the majority of the cases. A study at Columbia also reported that 90% of the study participants not sought any HCP after noticing the first symptom [24]. Henry and colleagues reported that participants who thought their symptoms were not serious had a threefold greater chance of waiting longer before consulting than those who did.…”
Section: Discussionmentioning
confidence: 99%
“…Ignorance of illness or waiting for the disappearance of the symptom by itself was the major reason for not seeking help in the majority of the cases. A study at Columbia also reported that 90% of the study participants not sought any HCP after noticing the first symptom [24]. Henry and colleagues reported that participants who thought their symptoms were not serious had a threefold greater chance of waiting longer before consulting than those who did.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection and timely treatment of leprosy are key for interrupting transmission and preventing physical and social complications and thus reducing disease burden [ 5 ]. However, as a relatively rare skin disease, early identification and diagnosis of leprosy patients remains a challenge, especially in low-endemic areas.…”
Section: Introductionmentioning
confidence: 99%
“…Estudo realizado no nordeste da Colômbia, sobre fatores associados ao atraso no diagnóstico da hanseníase, constatou que os homens eram mais diagnosticados com hanseníase, com atraso médio no diagnóstico da doença de 33,5 meses, na forma multibacilar e com grau 2 de incapacidade física no momento do diagnóstico 17 .…”
Section: Discussionunclassified